2016
DOI: 10.14260/jemds/2016/893
|View full text |Cite
|
Sign up to set email alerts
|

To Assess the Magnitude of Oxidative Stress and Antioxidant Defense in Preeclampsia

Abstract: Preeclampsia is a multifactorial disease. Recent studies show that free radical induced endothelial injury may be a factor in pathogenesis of preeclampsia and that a biochemical imbalance occurs with an increase of oxidative stress, lipoperoxidation a nd deficient antioxidants. AIMS AND OBJECTIVESTo evaluate parameters of oxidative stress and antioxidant defense in preeclampsia and thereby find any aetiological correlation. MATERIALS AND METHODSStudy was carried on pregnant and non-pregnant women placed in fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…It can lead to eclampsia if not promptly treated. Pre-eclampsia and eclampsia are greatly associated with maternal mortality and poor pregnancy outcomes 14 . The present study showed that 40 (13.0%) women in our study were pre-eclamptic while 269 (87%) were normotensive.…”
Section: Discussionmentioning
confidence: 99%
“…It can lead to eclampsia if not promptly treated. Pre-eclampsia and eclampsia are greatly associated with maternal mortality and poor pregnancy outcomes 14 . The present study showed that 40 (13.0%) women in our study were pre-eclamptic while 269 (87%) were normotensive.…”
Section: Discussionmentioning
confidence: 99%
“…A biochemical imbalance between the production of endogenous antioxidants and the production of free radicals is thought to occur in pregnant women with preeclampsia. This imbalance will lead to an increase in oxidative stress, lipid lipoperoxidation, superoxide anion radicals, and a deficiency of anti-oxidants [10]. If this generated oxidative stress overwhelms the natural protective antioxidant mechanism in the body, there will be an increase in trophoblastic turnover and subsequent release of harmful trophoblastic debris into the maternal circulation [11,12].…”
Section: Introductionmentioning
confidence: 99%